Pengaruh Integrasi Live Shopping Shopee terhadap Retensi Pelanggan dan Peningkatan Volume Penjualan UMKM dengan Mediasi Engagement Rate - Wandira, Novera; Dina Ratiana (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study examines the impact of the integration of Shopee's Live Shopping feature on customer retention and the increase in sales volume for Micro, Small, and Medium Enterprises (MSMEs), with engagement rate as a mediating variable. The approach used is quantitative associative with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. Data was collected from 100 active MSME sellers on the Shopee Live platform through an online questionnaire. The results show that the live shopping feature significantly enhances customer engagement through real-time interactions, which in turn contributes to increased customer retention rates and sales volume. The engagement rate, measured through the comment-to-view ratio, share ratio, and average watch duration, plays an important role as a mediator in this relationship. This study contributes to the growing literature on live commerce by providing empirical evidence from Indonesia's e-commerce ecosystem. Furthermore, the study offers practical insights for MSMEs to optimize their digital marketing strategies, particularly in the context of interactive social commerce in today's digital era.